Functional Biomaterials for Bone Regeneration: A Lesson in Complex Biology. (19th February 2020) - Armiento, Angela Rita; Hatt, Luan Phelipe; Sanchez Rosenberg, Guillermo; Thompson, Keith; Stoddart, Martin James
Abstract: Bone is a hard yet dynamic tissue with remarkable healing capacities. Research to date has greatly advanced the understanding of how bone heals and has led to marked success in the treatment of bone injuries. Nevertheless, the effective treatment of nonunions and large bone defects continues to present a challenge for orthopedic surgeons. Biomaterials provide researchers with a powerful instrument to potentially guide effective bone tissue regeneration in challenging healing environments. However, the most appropriate biomaterial for bone tissue engineering continues to be an area of intense debate. Indeed, the mechanical properties of real bone can be reproduced in vitro but the development of a functional bone substitute goes beyond the sole mechanical properties. The faithful reproduction of bone as a functional organ requires the combination of different cell types and temporal regulation of the molecular signaling involved during the different stages of bone formation and regeneration. This is not at all a trivial task. Herein, critical aspects of bone healing/regeneration including mechanical loading, inflammation, vascularization, and innervation are described. The success and the challenges behind the development of biomaterials, and the technologies used to functionalize them, in order to support the underlying cellular mechanisms are also highlighted. Abstract : Regeneration of large bone defects is a major clinical challenge. While biomaterials hold great promise and can potentially help many patients, translating this promise into the clinic is still proving problematic. Herein, the fundamental biological issues are highlighted together with examples of biomaterial manipulation of the underlying biology.